2016
DOI: 10.1177/1076029616634885
|View full text |Cite
|
Sign up to set email alerts
|

Plasma d-Dimer as a Useful Marker Predicts Severity of Atherosclerotic Lesion and Short-Term Outcome in Patients With Coronary Artery Disease

Abstract: Increased d-dimer is indicative of a hypercoagulable state and found to be associated with acute coronary syndromes. The present study aimed to evaluate whether plasma d-dimer levels could predict subsequent major clinical events in patients with coronary artery disease (CAD). First, 2209 angiographic-proven patients with CAD were consecutively enrolled. Then, all patients were subjected to follow up for an average of 18 months (ranged from 14 to 1037 days). The relationships of the plasma d-dimer with the sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 28 publications
0
27
1
Order By: Relevance
“…Therefore, we did not evaluate whether D-dimer levels could function as a monitoring marker and whether improvements in this biomarker would affect the ful predictor of major adverse cardiovascular events in patients with stable CAD. 7 The mean follow-up period of their study was shorter than in our study (18 vs. 73 month, respectively).…”
Section: Study Limitationscontrasting
confidence: 55%
“…Therefore, we did not evaluate whether D-dimer levels could function as a monitoring marker and whether improvements in this biomarker would affect the ful predictor of major adverse cardiovascular events in patients with stable CAD. 7 The mean follow-up period of their study was shorter than in our study (18 vs. 73 month, respectively).…”
Section: Study Limitationscontrasting
confidence: 55%
“…It has also been suggested that D-dimer may be an independent predictor of 2-year mortality after percutaneous coronary intervention in patients with coronary artery diseas [22]. D-dimer has also been shown to correlate with coronary SYNTAX II score and Gensini score in patients with coronary heart disease [4,23]. Creatinine is a metabolite of creatine, which is released during dephosphorylation to form creatinine and is excreted in the form of urine.…”
Section: Discussionmentioning
confidence: 99%
“…Results based on a prospective community-based atherosclerosis risk in communities study showed that people with high serum creatinine levels had an increased risk of coronary heart disease [26]. Serum creatinine levels have been shown to be an independent predictor of the severity and short-term outcome in patients with coronary artery disease [23,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…D-dimer is considered a useful biomarker because of its potential to identify individuals in a high coagulation state. D-dimer is often associated with thrombi, and its elevation should be of continuing concern [13][14][15] . D-dimer has been widely used in the diagnosis of VTE 8,16,17 .…”
Section: Discussionmentioning
confidence: 99%